1996
DOI: 10.1006/anbo.1996.0171
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Lettuce, Onion, and Red Beet. 1. Growth Analysis, Light Interception, and Radiation Use Efficiency

Abstract: A field experiment was carried out to analyse the growth of lettuce, onion and red beet in terms of : (a) canopy architecture, radiation interception and absorption ; (b) efficiency of conversion of absorbed radiation into biomass ; and (c) dry matter partitioning. Growth analysis, total solar radiation interception, PAR interception and absorption by the crop canopy, ground cover, maintenance respiration of onion bulbs and red beet storage roots were measured. Models for different leaf angle distribution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 29 publications
4
54
0
9
Order By: Relevance
“…Monteith (1977) was the first who demonstrated that biomass production, in cultivations with appropriate levels of irrigation and fertilization, depends linearly on the quantity of the absorbed light. This dependence is known and has been described in many papers (Warren-Wilson 1981;Jameison et al 1995;Tei et al 1996). Also in the described investigations, a linear correlation was found between the sum of photons absorbed during the period of growth of plants and the fresh mass yield (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Monteith (1977) was the first who demonstrated that biomass production, in cultivations with appropriate levels of irrigation and fertilization, depends linearly on the quantity of the absorbed light. This dependence is known and has been described in many papers (Warren-Wilson 1981;Jameison et al 1995;Tei et al 1996). Also in the described investigations, a linear correlation was found between the sum of photons absorbed during the period of growth of plants and the fresh mass yield (Fig.…”
Section: Resultssupporting
confidence: 78%
“…by Greenwood et al (1980). In European countries, onion is usually cultivated with higher plant density than in Finland and dry matter accumulations of 7000-13 000 kg ha -1 (Greenwood et al 1992) and 15 000 kg ha -1 (Tei et al 1996) have been reported with 30% higher plant populations compared to my experiment. Brewster (1990a) reports 10 000 to 12 000 kg ha -1 dry weights for spring-sown onion in his experiments, but considers 5000 kg ha -1 dry yield typical of practical farming.…”
Section: Plant Growth and Final Yieldmentioning
confidence: 47%
“…O acúmulo de massa seca na planta é resultado do balanço entre a radiação fotossinteticamente ativa incidente e a absorvida pelas folhas, da eficiência média de conversão da radiação absorvida em massa seca e da partição desta entre as partes coletoras de luz, as folhas, e o restante da planta (TEI et al, 1996). Portanto, a maior síntese de fotoassimilados e a partição equilibrada destes entre os diversos órgãos da planta, sob condições de pleno sol, proporcionaram maior precocidade no incremento e também na obtenção dos valores de máximo de massa seca de folha, caule, raiz, fruto e total em relação aos ambientes sombreados no meloeiro.…”
Section: Resultsunclassified